2013
DOI: 10.1177/0164027513508288
|View full text |Cite
|
Sign up to set email alerts
|

A Research Note on Age Discrimination and the Desire to Retire

Abstract: Age discrimination is a common problem in organizations. In our pilot study, we want to explore the processes how the desired retirement age is influenced by age discrimination and see psychological empowerment as an important mediator for the relationship between these variables. Data stem from an online questionnaire completed by 130 employees from different organizations in Germany (all 50 years or older). Our results show that age discrimination is an antecedent for the desired retirement age. It has a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
2
22
0
4
Order By: Relevance
“…Nevertheless, its consequences are not less harmful. On the contrary, as discrimination that fulfils ''objective'' criteria can remain completely unnoticed even by its victims (if it is taken for being justified or natural), it is often the perception of age discrimination that produces detrimental effects (higher psychological distress, Vogt Yuan 2007; lowered desired retirement age, Schermuly et al 2013). Accordingly, the identification of individual characteristics that increase the likelihood of the perception of age discrimination is of eminent importance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its consequences are not less harmful. On the contrary, as discrimination that fulfils ''objective'' criteria can remain completely unnoticed even by its victims (if it is taken for being justified or natural), it is often the perception of age discrimination that produces detrimental effects (higher psychological distress, Vogt Yuan 2007; lowered desired retirement age, Schermuly et al 2013). Accordingly, the identification of individual characteristics that increase the likelihood of the perception of age discrimination is of eminent importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ageism takes place in different areas of the workplace: Older workers are not being considered for job interviews (Furunes and Mykletun 2010); long term unemployment increasing from age 45 (Statistics Sweden 2017); they experience less wage increase (Brooke 2003); they receive less training and development and are passed over for promotion (Taylor and Walker 1998;Duncan and Loretto 2004;Krekula 2018) and they are disregarded when it comes to training for new technology (Furunes et al 2006). Studies show that ageism is related to intentions to resign or retire (Bennington 2001;Hofstetter and Cohen 2014;Schermuly et al 2014;von Hippel et al 2013), and that it constitutes a risk for long-term sickness and contributes to work disengagement (Volpone and Avery 2013). This indicates that the possibility and willingness to extend their working life is limited due to ageism in work organisations.…”
Section: Who Wants To Employ Older Workers?mentioning
confidence: 99%
“…Ageism, defined as discriminatory practices, attitudes and perceptions regarding older workers (Butler 1969), is still pervasive in many companies and organizations in the developed world (Rothenberg and Gardner 2011). In addition previous research has shown that experiencing stereotypes and discrimination at the workplace can influence older employees' productivity (Thorsen et al 2012), retirement intensions (Schermuly et al 2014), organizational commitment (Snape and Redman 2006), and work satisfaction (Orpen 1995). The individual perceptions of age discrimination may furthermore be amplified through the interaction with co-workers and supervisors and foster the prevalence of ageism at the organizational level.…”
Section: Setting the Scene: Ageism At The Workplacementioning
confidence: 99%